Review of Earned Value Management (EVM) tool for project management - Al-Affendi, Andy; Mohd Ariffin, Mohd Khairol Anuar (Research Publish Journals, 2018)
This paper presents a review of an Earned Value Management System (EVM) for assessing project performance compared to others methodology. This study attempts to solve problem to the project manager and project stake holder in handling complicated, dynamic and massive project information especially when changes to the project baseline which is unavoidable. Through feasibility review study, it has been shown that the EVM provide an objective measures of the work that project manager can access project achievement by converting the project data into manageable information clusters and in parallel promoting the earned value management method as an effective tool to monitor and control project constraints which are cost, timeline and scope.